Cakewalk : [large type] a novel - Brown, Rita Mae (Thorndike Press, 2016)
Continuing in the exuberant tradition of Six of One, Bingo , and Loose Lips, New York Times bestselling author Rita Mae Brown returns to her much-loved fictional hamlet of Runnymede, whose memorable citizens are welcoming both the end of the Great War and the beginning of a new era. The night a riot breaks out at the Capitol Theater movie house during a Mary Pickford picture, no less you can bet that the Hunsenmeir sisters, Louise and Julia, are nearby. Known locally as Wheezie and Juts, the inimitable, irrepressible, distinctly freethinking sisters and their delightful circle of friends are coming of age in a shifting world and are determined to understand their place in it. Across town, the well-to-do Chalfonte siblings are preparing for the upcoming wedding of brother Curtis. But for youngest sister Celeste, the celebration brings about a change she never expected and a lesson about love she ll not soon forget. Set against the backdrop of America emerging from World War I, Cakewalk is an outrageous and affecting novel about a small town where ideas of sin and virtue, love and sex, men and women, politics and religion, can be as divided as the Mason-Dixon Line that runs right through it and where there s no problem that can t be cured by a good yarn and an even better scotch.